2008
DOI: 10.1002/jcu.20457
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in renal hemodynamics in children with diabetes: Doppler sonographic findings

Abstract: Early changes in renal hemodynamics are detectable on Doppler sonography in children with diabetes without any evidence of renal dysfunction and may suggest a preclinical stage of diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
5
8
0
1
Order By: Relevance
“…ROC curve revealed that RI showed a sensitivity of 100% in the prediction of DN. Our results are in agreement with the results seen in type 1 diabetic patients of many previous studies that demonstrated increased resistivity indices early in the course of DN in the pre albuminuric stage [4, 16, 17]. Also, Masulli et al [18] reported similar results but in type 2 diabetic patients as they found that high RI is associated with features of DN and its progression over time, independent of albuminuria.…”
Section: Discussionsupporting
confidence: 93%
“…ROC curve revealed that RI showed a sensitivity of 100% in the prediction of DN. Our results are in agreement with the results seen in type 1 diabetic patients of many previous studies that demonstrated increased resistivity indices early in the course of DN in the pre albuminuric stage [4, 16, 17]. Also, Masulli et al [18] reported similar results but in type 2 diabetic patients as they found that high RI is associated with features of DN and its progression over time, independent of albuminuria.…”
Section: Discussionsupporting
confidence: 93%
“…The International Diabetic Nephropathy Study Group showed a correlation between higher blood pressures within the normal range and mesangial expansion in normoalbuminuric patients with DM1 [32]. Such subtle increases in arterial pressure may be of clinical importance in a condition like DM that results in abnormal autoregulation of pressure and flow in the kidney [33]. In the present study pubertal diabetics had higher blood pressure compared to pre-pubertal patients.…”
Section: Discussionsupporting
confidence: 53%
“…The renal Doppler RIs also correlated positively with diabetes duration. They concluded that Doppler sonography can be used to detect early changes in the hemodynamics of pediatric diabetics before any clinical indicators of kidney problems are evident [54]. An important finding was the positive and significant correlation between NO levels and the RIs which represent the early hemodynamic intrarenal changes.…”
Section: Discussionmentioning
confidence: 99%
“…However a strong correlation was identified to GFR (r = −0.2, p ≤ 0.01). Savino et al (18) mentioned that intrarenal hemodynamic abnormalities are detectable by Doppler ultrasonography even in early diabetic nephropathy before microalbuminuria appears and in a recent study by Pelliccia et al (29) they concluded that early changes in renal hemodynamics are detectable on Doppler sonography in children with diabetes without any evidence of renal dysfunction and may suggest a preclinical stage of diabetic nephropathy. In a study conducted on type 2 diabetic children by Mac Isaac et al (30) they concluded that subjects with type 2 diabetes and reduced glomerular filtration rate had similar degrees of intrarenal vascular disease, as measured by the intrarenal arterial resistance index, regardless of their albumin excretion rates status.…”
Section: Discussionmentioning
confidence: 99%